Strengthening Quranic Literacy and Islamic Character Through a Community-Based Participatory Approach at Rumah Peradaban Spirit Nabawiyah Community Fannaz - Mavianti Mavianti; Nurul Zahriani JF; Abdul Haris (Maslahah: Jurnal Pengabdian Masyarakat, 2026)
Quranic literacy strengthening in non-formal community settings represents a critical yet underexplored domain in Islamic education. This community service program aimed to strengthen Quranic literacy and Islamic character formation at Rumah Peradaban Spirit Nabawiyah Community Fannaz through a participatory community-based approach. Implemented over three months with 28 active participants aged 4-15 years, the program comprised four main interventions: structured Quran recitation, Islamic book literacy (Readathon Islami), prophetic storytelling (kisah Nabi), and community manager mentoring. Results showed significant improvements across all indicators. Consistent recitation (?5 times/week) rose from 32% to 82% of participants. Active participation in Islamic book discussions increased from 45% to 89%, and independent book borrowing grew from near-zero to 71%. Prophetic storytelling with a three-phase pedagogical design (opening-narrative-reflection) led to 91% of participants identifying Islamic character values, and 78% connecting them to real-life situations. The program also produced a community literacy guide as an institutional asset for sustainability. These findings confirm that structured, methodological, community-empowerment-centered approaches can effectively transform incidental religious practice into sustainable Quranic literacy movements in non-formal Islamic education.